Negative Politeness Strategies in English for Nusantara Textbook for Learners - Wahyuni, Sri; Issy Yuliasri; Rahayu Puji Haryanti (English Education Journal, 2024)
Politeness involves using the pragmatic approach that is most appropriate and specific to a given situation. Additionally, politeness is essential in making conversation, especially in the scope of the school, which builds the character of learners in the association. Furthermore, the textbook is an essential instrument for the teacher as an instructor to manage to convey the material in the classroom. The analysis of negative politeness strategies in English textbooks provides valuable insights into how these strategies help students understand approaches that avoid force or interrupt others' space, thereby fostering respect and minimizing potential threats to one's self-esteem or social status. Hence, this study aimed to analyze the use of negative politeness strategies in an English textbook entitled “English for Nusantara”. This study carried out a qualitative method with content analysis. Content analysis provided deep insight into how these strategies were implemented and how they influenced students' understanding of respectful and inclusive communication through English textbooks. The findings showed that three sub-strategies were realized in the book. They are questioning and hedging, giving deference, and apologizing. The dominant sub-strategy was found giving deference. The implication of giving deference, particularly through honorific expressions, suggests a strategy where speakers employ respectful language or titles when referring to the person they are addressing. Additionally, Questioning and hedging involved making requests a politely and using language that softens the impact of statements, indicating a degree of uncertainty or politeness. Meanwhile, apologizing plays a significant role in maintaining harmony and repairing relationships when misunderstanding occurs.